If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
3*x-(4*x)+3 = 6 // - 6
3*x-(4*x)-6+3 = 0
3*x-4*x-6+3 = 0
-x-3 = 0 // + 3
-x = 3 // * -1
x = -3
x = -3
| -12=a+2a+6 | | -4+2w+6w=-52 | | a+4-2a=14 | | 2b-4-6b=20 | | -6t+2+3t=-7 | | -4d+6+d=-18 | | m+4+2m=10 | | 7+4a+7a=95 | | 10+x-6x=10 | | -88=3k+6k+2 | | 10=6a-3a-5 | | 50=4d+2d-10 | | 2d+1+2d=-27 | | 3t+7+6t=70 | | -7+5m+7m=29 | | 7t-2+2t=88 | | -5n-8+2n=-8 | | -1-4x+5x=0 | | 2d+4+d=25 | | 64=7b+2b-8 | | 2b-6+3b=24 | | 8+3b+2b=-2 | | 2d+1+4d=37 | | 4-n-6n=11 | | -5k+6-6k=-49 | | 5-3a+a=-7 | | 4+7a-4a=10 | | -13=2x-3x-1 | | 4=-6b+3b+1 | | 8+6k-2k=4 | | -w-10-2w=-37 | | -5-3n-6n=-14 |